Graphene and CdS nanocomposite: A facile interface for construction of DNA-based electrochemical biosensor and its application to the determination of phenformin - Zeng, Lijiao; Wang, Rui; Zhu, Lihua; Zhang, Jingdong (Colloids and surfaces, B, Biointerfaces, 2013)
•Graphene/CdS nanocomposite was synthesized with a low temperature process.•GR-CdS possessed outstanding electrochemical performance for electron transfer.•Electrochemical response of DNA on electrode was significantly promoted by GR-CdS.•DNA/GR-CdS biosensor showed sensitive electrochemical response to phenformin. Graphene/cadmium sulphide (GR-CdS) nanocomposite was synthesized via a low temperature process in aqueous solution. The as-prepared nanocomposite was characterized by scanning electron microscopy, UV–visible spectroscopy, Fourier transform infrared spectroscopy, and X-ray diffraction. The impedance analysis indicated that GR-CdS nanocomposite possessed outstanding electrochemical performance for facile electron transfer. When DNA was immobilized on GR-CdS (DNA/GR-CdS) modified electrode, the electrochemical oxidation of guanine and adenine in DNA residue bases was significantly promoted. Due to the interaction of DNA with phenformin, the voltammetric current of guanine or adenine on the DNA/GR-CdS electrode was decreased when phenformin was present in the electrolytic solution. Under optimized conditions, the signal of guanine on DNA/GR-CdS electrode decreased linearly with increasing the concentration of phenformin in the range of 1.0×10−6molL−1 to 1.0×10−3molL−1. The proposed DNA-based electrochemical biosensor was successfully applied to the determination of phenformin in real samples.